Understanding the interaction between stunting and women’s autonomy - Fotarisman Zaluchu (Inovasi, 2022)
Stunting has a long and permanent impact. Until now, the analysis of the causes of stunting still does not provide a paradigm for women's autonomy. In this paper, it is explained that women's autonomy is rooted in low maternal education, young mother's age, low maternal weight, and domestic violence. These four factors represent the presence of women in relation to stunting based on the scientific literature obtained through the Pubmed database. Therefore, two things are recommended. First, it is necessary to improve health education not only for pregnant women but also for mothers-in-law and other household members in the household when the mother is pregnant and at the age of the baby <6 months. Second, it is necessary to increase husband's support for women during pregnancy and during the breastfeeding period.